Rekonstruksi Normatif Kontrak Kerja Agen Asuransi Jiwa: Integrasi Nilai Itikad Baik dalam Praktik Asuransi - Rasmiaty, Mia (LPPM Universitas Ekasakti Padang, 2024)
Insurance agents play a crucial role in the life insurance industry, serving as a bridge between companies and the public, explaining the benefits and terms of policies, and guiding the application process. The dynamics of agent employment often lead to legal issues, particularly concerning employment contracts with insurance companies, necessitating normative reconstruction to establish a balance of rights and obligations. The rapid growth of the insurance industry, alongside increasing legal challenges, underscores the importance of fair and balanced employment contracts to protect both parties. This study employs a normative juridical method. It finds that regulatory issues in the employment contracts of life insurance agents in Indonesia highlight the need for legal updates and clarification to prevent confusion and imbalance, often detrimental to agents. Deficiencies in regulation, as evident in the Insurance Law, require normative reconstruction to establish a clear and fair legal framework, including definitions, scopes of work, and oversight mechanisms. Such updates are expected to enhance justice, transparency, and public trust in the life insurance industry while more effectively protecting the rights of agents and consumers.